Clearing a Path: New Ways of Seeing Traditional Indigenous Art - Robertson, Carmen.; Farrell Racette, Sherry (University of Regina, Canadian Plains Research Center, 2009)
Catalogue d'exposition. This exhibition includes art from artists who live in all parts of Saskatchewan, from Wood Mountain in the south to Turner Lake in the north. From youth to elder, the artists mentor others to ensure the ongoing vitality of traditional arts in the province
Section: 80 p. : ill. en coul. ; 21 cm.
Keywords: _Nettoyé